Preterm Birth: Thoughtful Strategies for Screening and Management of Risk Factors: A Descriptive Review - Sarah Harris; Andrew Greene; Sarah Downs; Allie Sakowicz; Kristen H. Quinn; Jeff M. Denney (IMR Press, 2024)
Objective: Preterm delivery remains the leading cause of neonatal morbidity and mortality leading to a burden lasting well beyond the inherent costs of caring for the premature neonate. Physician-scientists, scientists, and clinicians have intensively studied associations, scoured every aspect to determine modifiable risk factors, and trialed prospective interventions to generate best practices. We aimed to generate a useful review for clinicians for the identification of women at risk for preterm birth along with modifiable factors and treatments to help reduce preterm delivery. Mechanism: We performed a literature search for preterm birth prevention to facilitate compilation of a narrative review. Findings in Brief: The PROLONG study found that Makena did not significantly reduce the risk of preterm birth (PTB) <35 weeks among those with a history of PTB <37 weeks; the PTB rate was 11.5% in the placebo group and 11.0% in the 17 alpha-hydroxyprogesterone caproate (17-OHP) group, (relative risk (RR) 0.95, 95% confidence interval (95% CI) 0.71-1.26, p = 0.72) and led to the American College of Obstetricians and Gynecologists to no longer recommend use of Makena for prevention of preterm birth. Nonetheless, a number of tools for screening and behavior modification remain for clinicians to utilize in patient care: (1) alabama Preterm Prevention project showed high negative predictive value of a cervical length in excess of 2.0 cm for delivery preterm birth, particularly in women with prior preterm birth less than 34 weeks (hazard ratio (HR) 2.8, p < 0.0001; RR 2.1, p < 0.0001); (2) treatment of infections; e.g., antibiotic treatment of urinary tract infections may be associated with a reduction in preterm birth (RR 0.34, 95% CI 0.13-0.88); (3) discontinuation of tobacco and illicit drug use given the association of use with preterm birth; and (4) identification of vaginal dysbiosis or pathologic alterations in vaginal flora poses as opportunity to reduce preterm delivery (e.g., bacterial vaginosis confers 2.9 fold increased risk of preterm birth). Conclusions: Many associations and modifiable behaviors and conditions have been identified for the care of the patient at risk for preterm birth. Evidence-based therapeutic intervention includes identification and treatment of nutritional deficits, infections, short cervix, and cervical insufficiency. Future studies on alteration of vaginal microbiome may identify additional therapy to reduce incidence of preterm birth.